Lithospheric Structure of the Pampean Flat Slab Region from Double-Difference Tomography - Linkimer Abarca, Lepolt (2019)
We obtain earthquake locations and a detailed three-dimensional velocity model of the flat slab subduction zone in west-central Argentina (latitudes: 32-30°S and longitudes: 70-66°W) using a regional-scale doubledifference tomography algorithm with earthquake data recorded by the SIEMBRA (2007–2009) and ESP (2008–2010) broadband seismic networks. In this region, the flat subduction of the Nazca Plate including the Juan Fernandez Ridge is spatially correlated with a volcanic gap and the basement-cored uplifts of the Sierras Pampeanas in the overriding South American Plate. Our results show the subducting Nazca Plate as a continuous band of mostly increased P-wave velocities coinciding with the Wadati-Benioff Zone. In the overriding South American Plate, the lithospheric mantle appears to be heterogeneous but mostly characterized by a ratio between P- and S-wave velocities (Vp/Vs) of 1.75–1.77, which is consistent with depleted peridotites. Two Vp/Vs anomalies deviate from this mantle with lower (1.70–1.73) and higher (1.78–1.82) Vp/Vs, which are interpreted as localized dry and hydrated regions, respectively. The lower Vp/ Vs is consistent with an enrichment of 40–80% of orthopyroxene and the higher Vp/Vs with up to 5% mantle hydration. The size, orientation, and location of these seismic anomalies suggest the progressive eastward dehydration of the subducting slab and the presence of an east-dipping large-scale lithospheric suture, which is interpreted as evidence of an ancient subduction zone and also as a weak zone that facilitates the hydration of the upper plate. Our inversion results suggest a thicker South American crust in the Western Sierras Pampeanas and the partial eclogitization of the lower crust beneath that region where velocities match three types of eclogites at depths of 40–60 km. In the middle-to-upper crust, velocities are reduced in the Precordillera and Vp/Vs is higher in the Cuyania and Chilenia terranes (> 1.75) than in the Pampia terrane (1.67–1.75). These observations are consistent with the presence of a thick carbonate sequence in the Precordillera, mafic-ultramafic rocks in Cuyania and Chilenia, and felsic rocks in Pampia. The higher variability in Vp/Vs and strong velocity changes at crustal depths within the Precordillera and the Cuyania Terrane agree with more complexity in crustal structure for these regions and reveal two mid-crustal discontinuities as well as the Chilenia-Precordillera suture zone. Finally, the relocated slab earthquakes refine the slab geometry and suggest that at depths of ~100 km, the flat slab segment is ~240 km wide and has a slight westward dip (~2°) before it resumes its descent into the mantle with a steep angle (~25°). The observation of a wider flat slab segment than the width of the Juan Fernandez Ridge offshore (~100 km) implies that there might be additional contributing factors for the flattening besides the subduction of the overthickened oceanic crust.